2010
DOI: 10.3858/emm.2010.42.4.025
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AMP-activated protein kinase stimulates the nuclear localization of glyceraldehyde 3-phosphate dehydrogenase in human diploid fibroblasts

Abstract: In addition to its well-known glycolytic activity, GAPDH displays multiple functions, such as nuclear RNA export, DNA replication and repair, and apoptotic cell death. This functional diversity depends on its intracellular localization. In this study, we explored the signal transduction pathways involved in the nuclear translocation of GAPDH using confocal laser scanning microscopy of immunostained human diploid fibroblasts (HDFs). GAPDH was present mainly in the cytoplasm when cultured with 10% FBS. Serum dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 42 publications
3
27
0
Order By: Relevance
“…34 Furthermore, also AMPK has been shown to stimulate GAPDH translocation into the nuclei. 36 Our data showed that both NAC and CC inhibited GAPDH nuclear translocation, demonstrating that this event was mediated by both ROS and AMPK.…”
Section: Discussionmentioning
confidence: 50%
“…34 Furthermore, also AMPK has been shown to stimulate GAPDH translocation into the nuclei. 36 Our data showed that both NAC and CC inhibited GAPDH nuclear translocation, demonstrating that this event was mediated by both ROS and AMPK.…”
Section: Discussionmentioning
confidence: 50%
“…Inhibition of PI3K/AKT signaling can block the nuclear export of GAPDH (28), suggesting that PI3K/AKT negatively regulates nuclear GAPDH localization. We therefore asked if inhibition of AKT would mimic CIB1 depletion and induce GAPDH nuclear accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed signaling pathways that are involved in the translocation of GAPDH to and from the nucleus are illustrated. AMPK (for, AMP-activated protein kinase) activity results in a net influx of GAPDH to the nucleus [99], whereas the PI3K/Akt and Akt2 pathways allow for a net efflux from the nucleus [99,100]. Dotted lines represent the intermediate signals from the initial cell stimuli.…”
Section: Translocation To the Nucleusmentioning
confidence: 99%
“…As one navigates through this book, one will notice that GAPDH is involved in some way to many of the proteins and events that just were mentioned as being associated with the overall process of insulin signaling and GLUT4-membrane trafficking, including PI3K, Akt [98][99][100], Rab proteins [101][102][103], cytoskeletal components (namely, microtubules and actin microfilaments; see Sect. 4.2.1), membrane fusion and clathrin-coated vesicles [104].…”
Section: Glut4 Transportermentioning
confidence: 99%
See 1 more Smart Citation